Synthesis of pomegranate-shaped micron ZnMn2O4 with enhanced lithium storage capability - Ying Zhang; Pu Zhang; Yue Xu; Xiaolan Song; Hui Wang; Ting Ma (Journal of Materiomics, 2021)
As high capacity anode materials, spinel-type transition metal oxides have a bottleneck of poor cyclic stability. Nano structure and carbon loading are common modification approaches, while the high cost is unaffordable for industrial implementation. In this study, micron scale zinc manganate was synthesized by solvothermal plus calcination process. The pomegranate-shaped ZnMn2O4 (p-ZMO) was obtained using solvent of ethylene glycol, and the microsphere-shaped ZnMn2O4 (m-ZMO) was obtained using water. During electrochemical testing, the p-ZMO anode delivered larger charge capacity of 726 mAh g−1 at 0.2 A g−1 than 589 mAh g−1 of m-ZMO. Even over 1000 cycles at 1 A g−1, the p-ZMO still maintained a reversible capacity of 506 mAh g−1 (much higher than 372 mAh g−1 of graphite anode), with a superior retention of 84%. It indicates that this work develops an effective strategy to prepare high-performance transition metal oxides for anode materials of lithium-ion batteries.